2007
DOI: 10.4049/jimmunol.178.12.7649
|View full text |Cite
|
Sign up to set email alerts
|

CD8+ T Cell-Mediated Suppression of Autoimmunity in a Murine Lupus Model of Peptide-Induced Immune Tolerance Depends on Foxp3 Expression

Abstract: Systemic lupus erythematosus is an autoimmune disease caused by autoantibodies, including IgG anti-DNA. New Zealand Black/New Zealand White F1 female mice, a model of spontaneous polygenic systemic lupus erythematosus, tolerized with an artificial peptide (pConsensus) based on anti-DNA IgG sequences containing MHC class I and class II T cell determinants, develop regulatory CD4+CD25+ T cells and CD8+ inhibitory T cells (CD8+ Ti), both of which suppress autoantibody production. CD8+ Ti inhibit primarily via sec… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

2
151
1

Year Published

2008
2008
2019
2019

Publication Types

Select...
6

Relationship

2
4

Authors

Journals

citations
Cited by 98 publications
(154 citation statements)
references
References 43 publications
2
151
1
Order By: Relevance
“…Table shows CD8 genes differentially expressed in naive vs pCons-treated mice We have long been interested in the role of CD8 þ T cells in murine lupus and in their specific role in the system of pCons-induced tolerance. 5,7,[24][25][26] The analysis of CD8 þ T cells from naive vs pCons-treated mice indicated that 60 genes were differentially expressed in this cell subset ( Figure 1a). Gene and condition clustering of CD8 þ T cells showed that large numbers of genes were downregulated in naive cells with higher expression in tolerized cells ( Figure 1a bottom two lines).…”
Section: Differential Gene Expression In Splenic Wbc From Naive Vs Pcmentioning
confidence: 99%
See 4 more Smart Citations
“…Table shows CD8 genes differentially expressed in naive vs pCons-treated mice We have long been interested in the role of CD8 þ T cells in murine lupus and in their specific role in the system of pCons-induced tolerance. 5,7,[24][25][26] The analysis of CD8 þ T cells from naive vs pCons-treated mice indicated that 60 genes were differentially expressed in this cell subset ( Figure 1a). Gene and condition clustering of CD8 þ T cells showed that large numbers of genes were downregulated in naive cells with higher expression in tolerized cells ( Figure 1a bottom two lines).…”
Section: Differential Gene Expression In Splenic Wbc From Naive Vs Pcmentioning
confidence: 99%
“…We have shown previously that interference with the expression of this gene via siRNA abrogated 60-70% of the suppressive capacity of the CD8 þ T cells from tolerized mice. 7,24,25 Silencing of one gene (Bcl2) in CD8 þ T cells from tolerized mice does not effect expression of other selected genes known to be involved (or not) in the suppressive capacity of CD8 þ Treg in our system To test whether silencing of bcl2 in tolerized CD8 þ T cells affects expression of other genes, we silenced tolerized CD8 þ T cells with different siRNA as described in the Materials and methods section and in the figure legends. Results shown in Figure 5 illustrate that silencing of bcl2 did not significantly affect the expression of other genes studied.…”
Section: Reproducibilitymentioning
confidence: 99%
See 3 more Smart Citations